SERVICE QUALITY ASSESSMENT FOR SUSTAINABLE HOUSEHOLD WASTE MANAGEMENT IN SINJAI DISTRICT, INDONESIA - Teuku Raja Fahsul Falah; Muhammad Hatta Jamil; Eymal B. Demmallino; Ariady Arsal; Yenita Sandra Sari; Hussein Alkhozahe; Cenap Ozel (Universitas Trisakti, 2025)
The rapid population growth in the region has led to challenges in managing household waste. Local governments must consider waste treatment infrastructure and landfill space availability when providing services. Aim: This study aims to evaluate the quality of services in household waste management in Sinjai District, Indonesia. Methodology and results: This study employs a mixed-method analysis utilizing the Delphi and SERVQUAL techniques. The research was conducted in Sinjai District, South Sulawesi, Indonesia, with a sample size of 397 respondents. The findings indicate that waste management within the Tondong landfill service coverage area in Sinjai Regency is relatively effective in reducing waste generation. According to the SERVQUAL analysis, apart from the tangible dimension, all other dimensions exhibit a negative GAP score, highlighting the need for improvements in each area. Conclusions, Significance, and impact of The Study: Waste management in Sinjai District, particularly in terms of composting and waste bank initiatives, faces major challenges in infrastructure, technology, and public awareness. Landfilling and composting methods are widely applied, but their efficiency needs to be improved. In the system, collection and transportation remain constrained by limited resources, while recycling requires community participation supported by education and wider access to recycling facilities. An integrated approach, involving the government, community, and private sector, is needed in Sinjai Regency to enhance the sustainability and effectiveness of waste management.